(untitled) (Prithvi Journal of Research and Innovation, 2021)
A merger includes two relatively equal entities that are combined to form one legal entity worth more than a sum of its two separate parts. In the last few years, many Nepali financial institutions have been consolidating through mergers and acquisitions. This paper aims to investigate how the stock market reacts when financial institutions announce mergers and acquisitions. This paper also examines the impact of cross-sectional variables on the abnormal returns obtained around merger announcements. The study covers 22 successful merger deals that occurred among 48 financial institutions over the period of 2004 to 2013. This paper used the event study method based on the market model to derive abnormal returns associated around the merger announcement date. The event dates are specified as the dates on which the mergers and acquisitions were announced. The results show that leaving a very few exceptional cases, none of the merged financial institutions received significant cumulative abnormal returns on the merger announcements, regardless of the use of different event periods. The cross-sectional regressions show that the pre-merger performance of target and relative market value are the significant influencing variables on acquirers’ cumulative abnormal returns. The finding implies that Nepali financial institutions merge merely to increase their capital base without producing any synergistic effect. Therefore, they need strategic plans for choosing the right partner and achieving other benefits like synergy effect, economies of scale and cost reduction from mergers and acquisitions.